EMPOWERMENT AS A CULTURE AND A STRATEGY TO STRENGTHEN THE ACTIVITIES OF RESEARCH AND INNOVATION: PROPOSAL OF A METHODOLOGY - Heriberto Niccolas Morales; Jaime Garnica Gonzalez; Arturo Torres Mendoza; German Resendiz Lopez (European Scientific Journal, ESJ, 2014)
This paper presents a proposal for a methodology to guide the implementation process of Empowerment in organizations that manage research and innovation activities in developing regions. It seeks to motivate the interest of research and innovative knowledge application groups use the Empowerment as a culture and a strategy of management in the Organization, looking for the operational flexibility to participate in the economic development of the region where they operate. The proposed methodology to guide the implementation process, aims to provide support to the manager or head of department to provide it with the essential principles that should know and follow in an exercise for improving the organization supported by empowerment. The structure of the methodology incorporates input from consultants and academics who have addressed and practiced empowerment approach successfully in other countries. Our academic interest has been to integrate these proposals with the adaptations that are considered relevant to organizations in developing countries.